Soldiers standing outside of U.S. Army barracks, Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Front of barracks. Nome" Original image in Hegg Album 18, page 12. Original photograph by Eric A. Hegg 1231; copied by Webster and Stevens 262.A